Cost-Effectiveness Analysis of Influenza A (H1N1) Chemoprophylaxis in Brazil - Vecoso, Luisa von Zuben; Silva, Marcus Tolentino; Resende, Mariangela Ribeiro; da Silva, Everton Nunes; Galvao, Tais Freire (Frontiers in Pharmacology, 2019)
BACKGROUND: Influenza A (H1N1) contributes to morbidity and mortality by severe influenza. Oseltamivir and zanamivir are recommended for treating and preventing influenza worldwide. In Brazil, this official recommendation lacks an economic evaluation. Our objective was to assess the efficiency of influenza A chemoprophylaxis in the Brazilian context. METHODS: We assessed the cost-effectiveness of oseltamivir and zanamivir for prophylaxis of influenza for high risk population, compared to no prophylaxis, in the perspective of Brazilian public health system. Quality-adjusted life years (QALY) and effectiveness data were based on literature review and costs in Brazilian real (BRL) were estimated from official sources and micro-costing of 2016’s H1N1 admissions at a university hospital. We used a decision-tree model considering prophylaxis and no prophylaxis and the probabilities of H1N1, ambulatory care, admission to hospital, intensive care, patient discharge and death. Adherence and adverse events from prophylaxis were included. Incremental cost-effectiveness ratio was converted to 2016 United States dollar (USD).Uncertainty was assessed with univariated and probabilistic sensitivity analysis. RESULTS: Adherence to prophylaxis was 0.70 (confidence interval [CI] 95% 0.54; 0.83); adverse events, 0.09 (CI 95% 0.02; 0.18); relative risk of H1N1 in chemoprophylaxis, 0.43 (CI 95% 0.33; 0.57); incidence of H1N1, 0.14 (CI 95% 0.11; 0.16); ambulatory care, 0.67 (CI 95% 0.58; 0.75); hospital admission,0.43 (CI 95% 0.39; 0.42); hospital mortality, 0.14 (CI 95% 0.12; 0.15); intensive care unit admission, 0.23 (CI 95% 0.20; 0.27); and intensive care mortality, 0.40 (CI 95% 0.29; 0.52). QALY in H1N1 state was 0.50 (CI 95% 0.46; 0.53); in H1N1 inpatients, 0.23 (CI 95% 0.18; 0.28); healthy, 0.885 (CI 95% 0.879; 0.891); death, 0. Adverse events estimated to affect QALY in -0.185 (CI 95% -0.290; -0.050). Cost for chemoprophylaxis was BRL 39.42 (standard deviation [SD] 17.94); ambulatory care, BRL 12.47 (SD 5.21); hospital admission, BRL 5,727.59 (SD 7,758.28); intensive care admission, BRL 19,217.25 (SD 7,917.33); and adverse events, BRL 292.05 (SD 724.95). Incremental cost-effectiveness ratio was BRL-4,080.63 (USD -1,263.74)/QALY and -982.39 (USD -304.24)/H1N1 prevented. Results were robust to sensitivity analysis. CONCLUSION: Chemoprophylaxis of influenza A (H1N1) is cost-saving in Brazilian health system context.